2005
DOI: 10.1002/app.21570
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and some properties of ionomers from a sulfonated styrene–butadiene–styrene triblock copolymer without gelation

Abstract: ABSTRACT:The conditions for the sulfonation of a highly unsaturated styrene-butadiene-styrene triblock copolymer (SBS) in cyclohexane containing a small amount of acetone with acetyl sulfate made by sulfuric acid and acetic anhydride without gelation were studied. After neutralization with metallic ions, the ionomers were characterized with IR spectrophotometry, dynamic mechanical analysis, and transmission electron microscopy. The melt flow, solution properties, and mechanical properties of the ionomers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…A slight excess of acetic anhydride relative to sulfuric acid (Ac 2 O/H 2 SO 4 = 1.1-2.0) is usually used to scavenge a small amount of water present in H 2 SO 4 . On the other hand, a higher excess can lead to the side reaction, as reported in the literature [14]. The acetyl sulfate formation is an equilibrium reaction depending on temperature.…”
Section: Synthesis Isolation and Solubilization Of The Sulfonated Psmentioning
confidence: 63%
See 1 more Smart Citation
“…A slight excess of acetic anhydride relative to sulfuric acid (Ac 2 O/H 2 SO 4 = 1.1-2.0) is usually used to scavenge a small amount of water present in H 2 SO 4 . On the other hand, a higher excess can lead to the side reaction, as reported in the literature [14]. The acetyl sulfate formation is an equilibrium reaction depending on temperature.…”
Section: Synthesis Isolation and Solubilization Of The Sulfonated Psmentioning
confidence: 63%
“…Thus, sulfonation of styrene homopolymer [3][4][5][6][7], styrene-ethene (propene, butene) [8][9][10][11][12][13], styrene-butadiene [14][15][16][17], and styrene-isobutylene [18][19][20] copolymers has been described and the resulting sulfonated (co)polymers have been intensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the suitable conditions, the melt flow, solution viscosity and mechanical properties of the polar functionalized SBS were also investigated. Xie et al also reported the enhancement in mechanical properties of polar functionalized SBS compared to pristine polymer and illustrated the decreasing ionic potential of mono valent and divalent cations present in the corresponding salt of ionomer decrease the melt viscosities 12 .…”
Section: Introductionmentioning
confidence: 96%
“…Moreover several papers related to sulfonation of rubber like polymers have been published. For instance, Xie et al investigated several properties like melt flow, solution viscosity, and mechanical properties of polar functionalized styrene-butadiene-styrene (SBS) triblock copolymer which has significant applications like adhesives for polar substances and compatibilizers for blends of polar and non-polar polymers 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation